An equilibrium analysis of efficiency gains from mergers - Dragan Jovanovic; Christian Wey (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2012)
We analyze the efficiency defense in merger control. First, we show that the relationship between exogenous efficiency gains and social welfare can be non-monotone. Second, we consider both endogenous mergers and endogenous efficiencies and find that merger proposals are largely aligned with a proper social welfare analysis which explicitly considers the without merger counterfactual. We demonstrate that the merger specificity requirement does not help much to select socially desirable mergers; to the contrary, it may frustrate desirable mergers inducing firms not to claim efficiencies at all.
Keywords: K21; L13; L41; 330; Horizontal Mergers; Efficiency Defense; Merger Specific Efficiencies; Horizontale Konzentration; Fusion; Wirtschaftliche Effizienz; Fusionskontrolle; Wohlfahrtsanalyse; Theorie